Analisis Perencanaan dan Pengembangan Desa Wisata Pantai Lon Malang - Vionanda Aprilia; Tripitono Adi Prabowo (Jurnal Etnik: Ekonomi-Teknik, 2022)
The tourism sector in Indonesia is increasingly experiencing development. The opening of tourist attractions that are increasing can increase the income of an area and open jobs for the community. However, in its development, a development planning process is needed that is in accordance with the core stages of development planning and its development must be based on the expectations that are aligned with the community, namely to improve welfare. One of the tourist destinations that is currently popular and is of concern to many Madura Island tourists today is Lon Malang Beach Tourism Village located in Sampang Regency, Madura Island. Therefore researchers will conduct further research related to the planning and development of the Lon Malang Beach Tourism Village. This study aims to analyze planning and development in the Pantai Lon Malang Tourism Village so that the success of the planning process in a development project carried out by local apparatus and the local community can be identified. The scope of this research includes: (1) The planning process for the development planning of Lon Malang Beach Tourism Village; (2) Effectiveness in the development activities of Lon Malang Beach Tourism Village. Using descriptive qualitative methods with data collection techniques using in-depth interviews, observation, literature studies and documentation to reveal the process of development planning stages and the effectiveness of development activities in the Lon Malang Beach Tourism Village.